Genomics‐Driven Discovery of a Novel Glutarimide Antibiotic from Burkholderia gladioli Reveals an Unusual Polyketide Synthase Chain Release Mechanism. (26th October 2020) - Nakou, Ioanna T.; Jenner, Matthew; Dashti, Yousef; Romero‐Canelón, Isolda; Masschelein, Joleen; Mahenthiralingam, Eshwar; Challis, Gregory L.
Abstract: A gene cluster encoding a cryptic trans‐acyl transferase polyketide synthase (PKS) was identified in the genomes of Burkholderia gladioli BCC0238 and BCC1622, both isolated from the lungs of cystic fibrosis patients. Bioinfomatics analyses indicated the PKS assembles a novel member of the glutarimide class of antibiotics, hitherto only isolated from Streptomyces species. Screening of a range of growth parameters led to the identification of gladiostatin, the metabolic product of the PKS. NMR spectroscopic analysis revealed that gladiostatin, which has promising activity against several human cancer cell lines and inhibits tumor cell migration, contains an unusual 2‐acyl‐4‐hydroxy‐3‐methylbutenolide in addition to the glutarimide pharmacophore. An AfsA‐like domain at the C‐terminus of the PKS was shown to catalyze condensation of 3‐ketothioesters with dihydroxyacetone phosphate, thus indicating it plays a key role in polyketide chain release and butenolide formation. Abstract : Genome mining enabled the discovery of gladiostatin, a novel glutarimide antibiotic from the cystic fibrosis associated bacterium Burkholderia gladioli . Gladiostatin contains an unusual 2‐acyl‐3‐hydroxy‐4‐methylbutenolide and exhibits promising activity against human cancer cells. The polyketide synthase responsible for its biosynthesis employs a novel mechanism for chain release, resulting in formation of a phosphorylated butenolide intermediate.